Esterification of Free Fatty Acid in Crude Palm Oil Off Grade - Supardan, Muhammad Dani; Satriana, Satriana (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2009)
The esterification of free fatty acids (FFA) found in crude palm oil (CPO) off grade with methanol is a promising technique to convert FFA into valuable fatty acid methyl ester (FAME, biodiesel) and obtain a FFA-free oil that can be further transesterified using alkali bases. In this work, the effects of the main variables involved in the esterification process i.e. alcohol to oil molar ratio, reaction temperature, agitation speed and the initial amount of FFA of oil, were studied in the presence of sulphuric acid as catalyst at concentration of 1%-w. The experimental results show that the esterification process could lead to a practical and cost effective FFA removal unit in front of typical oil transesterification for biodiesel production.Keywords: CPO off grade, esterification, free fatty acid